2023
DOI: 10.3389/fimmu.2022.933347
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular mRNA BNT162b2 vaccine against SARS-CoV-2 induces neutralizing salivary IgA

Abstract: Intramuscularly administered vaccines stimulate robust serum neutralizing antibodies, yet they are often less competent in eliciting sustainable “sterilizing immunity” at the mucosal level. Our study uncovers a strong temporary neutralizing mucosal component of immunity, emanating from intramuscular administration of an mRNA vaccine. We show that saliva of BNT162b2 vaccinees contains temporary IgA targeting the receptor-binding domain (RBD) of severe acute respiratory syndrome coronavirus-2 spike protein and d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 134 publications
2
11
0
Order By: Relevance
“…In this study, we observed that the titers of anti‐N‐specific IgG in the BAL samples of both groups showed stable and slightly upward trend at 6–10 weeks post prime immunization, although the levels in the N‐Ferritin group were significantly higher than those in the N group. Although the anti‐N‐specific IgA levels in the BAL samples of the N‐Ferritin group were higher, the IgA levels within the immune groups were much lower than those of the IgG, and these results were consistent with previous studies 39,40 . In summary, using nanoparticles as antigens can effectively improve the levels of anti‐N‐specific IgG and IgA in the lungs, which might be beneficial for reducing the probability of severe pneumonia.…”
Section: Disscussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, we observed that the titers of anti‐N‐specific IgG in the BAL samples of both groups showed stable and slightly upward trend at 6–10 weeks post prime immunization, although the levels in the N‐Ferritin group were significantly higher than those in the N group. Although the anti‐N‐specific IgA levels in the BAL samples of the N‐Ferritin group were higher, the IgA levels within the immune groups were much lower than those of the IgG, and these results were consistent with previous studies 39,40 . In summary, using nanoparticles as antigens can effectively improve the levels of anti‐N‐specific IgG and IgA in the lungs, which might be beneficial for reducing the probability of severe pneumonia.…”
Section: Disscussionsupporting
confidence: 90%
“…Although the anti-Nspecific IgA levels in the BAL samples of the N-Ferritin group were higher, the IgA levels within the immune groups were much lower than those of the IgG, and these results were consistent with previous studies. 39,40 In summary, using nanoparticles as antigens can effectively improve the levels of anti-N-specific IgG and IgA in the lungs, which might be beneficial for reducing the probability of severe pneumonia.…”
Section: Disscussionmentioning
confidence: 99%
“…Importantly, we limited the study to individuals vaccinated at the beginning of the pandemic to select a substantial number of confirmed SARS-CoV-2-naive participants to be included in the study. Since SARS-CoV-2 infection became extremely prevalent in Europe and in the US, we speculate that some of the previous inconsistencies reported in the literature [3][4][5][6][7][8][9][10][11] on saliva IgA responses might relate to difficulties recruiting participants who were truly SARS-CoV-2 naive. Many SARS-CoV-2 infections are indeed asymptomatic and even more so in the recent phases of virus circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies conclude that humoral mucosal immunity is largely driven by previous infection, with little impact of vaccination, 4 , 5 , 6 while others suggest that mRNA vaccination can by itself elicit long-lasting anti–SARS-CoV-2 mucosal IgA responses. 7 , 8 , 9 , 10 , 11 Herein, we compared individuals with previous SARS-CoV-2 infection and SARS-CoV-2–naive individuals included in the CoviCompare P and CoviCompare M vaccination trials 12 for their saliva and serum responses after 2 different modes of antigenic challenge: infection and vaccination or vaccination alone.…”
Section: Introductionmentioning
confidence: 99%
“…While the systemic IgG response after vaccination has been studied in great detail, aspects of mucosal immunity after intramuscular vaccination against SARS-CoV-2 have been analyzed less extensively and yielded partially contradictory results. For example, BNT vaccine was reported to induce IgG and little or no specific IgA in the saliva with unclear neutralizing activity ( 14 ), while others reported the induction of both SARS-CoV-2-specific IgG and mucosal IgA after vaccination ( 15 18 ). Yet another study described systemic, but not mucosal SARS-CoV-2-specific Ig after vaccination ( 19 ).…”
Section: Introductionmentioning
confidence: 99%